Pemberdayaan Masyarakat Berbasis Kearifan Lokal Melalui Pelatihan Pembuatan Hiasan Bunga Dari Kelobot Jagung - Sri Hartini; Novenda Pramesti Ayuningtyas; Fidela Novitasari; Stelly Revina Prabowo; Dwi Novianti; Bakti Kresno Wibowo (Universitas Kristen Satya Wacana Salatiga, 2020)
Community service activities are carried out in Kalkurmo Village, Beringin District, Semarang Regency. This activity is aimed at empowering the community through processing the jaging husk waste into decorative products with economic value. Activities are carried out in the form of training and mentoring until they become products. So far, corn husks, which have been used only as animal feed or baked goods, can actually be processed into decorative products with economic value. This activity is expected to motivate the people of Kalikurmo Village to use waste materials into products of economic value so that they can improve community welfare.